2020
DOI: 10.1007/s00167-020-06025-1
|View full text |Cite
|
Sign up to set email alerts
|

Coronal shaft bowing of the femur affects varus inclination of the surgical transepicondylar axis in varus knee osteoarthritis

Abstract: PurposeThis study investigated the relationship between femoral shaft bowing and the orientation of the surgical transepicondylar axis (TEA) in the coronal plane in varus knee osteoarthritis (OA). MethodsA total of 82 knees scheduled to undergo total knee arthroplasty (TKA) for the treatment of varus knee OA were enrolled. The hip–knee‐ankle angle (HKA) was measured preoperatively on anteroposterior whole‐leg standing radiographs. The lateral angle between the TEA and the mechanical axis of the femur (MA‐TEA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 14 publications
4
21
0
Order By: Relevance
“…indicated that sTEA was perpendicular to femoral mechanical axis in the coronal plane after a study of 60 Japanese OA knees. However, they did not clarify the lower extremity alignment and femoral bowing of the patients, which are very common in Asian populations and may have an effect on the coronal orientation of sTEA 8,13 . This study found that the sTEA coronal angle was widely distributed and was influenced by femoral bowing, especially lateral femoral bowing.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…indicated that sTEA was perpendicular to femoral mechanical axis in the coronal plane after a study of 60 Japanese OA knees. However, they did not clarify the lower extremity alignment and femoral bowing of the patients, which are very common in Asian populations and may have an effect on the coronal orientation of sTEA 8,13 . This study found that the sTEA coronal angle was widely distributed and was influenced by femoral bowing, especially lateral femoral bowing.…”
Section: Discussionmentioning
confidence: 64%
“…The sTEA has long been considered the closest reference axis to knee flexion‐extension axis that can be used in clinical practice 5,7 . The orientation of sTEA in coronal plane is believed to be perpendicular to mechanical axis, 6,7 which makes sTEA play an important role in the treatment of patients with bone defects and TKA revisions since the availability of original anatomical landmarks is limited 8 . Kobayashi et al 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In daily practice, we often see anterior and lateral bowing of the femur [1]. The bowing of the femur might affect the surgical plan and outcomes in cases requiring internal fixation surgery for fractures [2,3], or implant insertion for hip and knee arthroplasty [4,5]. Several reports have shown that femoral bowing is correlated with patient characteristics such as aging, race, osteoarthritis, and osteoporosis [1,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%